Does the Etiology, Phenomenology and Motor Subtype of Delirium Differ When It Occurs in Patients With An Underlying Dementia?: A Multi-Site, International Study - Glynn, Kevin; McKenna, Frank; Lally, Kevin; Grover, Sandeep; Chakrabarti, Subho; Mattoo, Surendra K.; Avasthi, Ajita; Sharma, Akhilesh; Adamis, Dimitrios; Awan, Fahad; Dunne, Colum P.; McFarland, John; et al. (Journal of geriatric psychiatry and neurology, 2024)
Objectives To compare the etiology, phenomenology and motor subtype of delirium in patients with and without an underlying dementia. Methods A combined dataset (n = 992) was collated from two databases of older adults (>65 years) from liaison psychiatry and palliative care populations in Ireland and India. Phenomenology and severity of delirium were analysed using the Delirium Symptom Rating Scale Revised (DRS-R98) and contributory etiologies for the delirium groups were ascertained using the Delirium Etiology Checklist (DEC). Delirium motor subtype was documented using the abbreviated version of the Delirium Motor Subtype Scale (DMSS4). Results Delirium superimposed on dementia (DSD) showed greater impairment in short term memory, long term memory and visuospatial ability than the delirium group but showed significantly less perceptual disturbance, temporal onset and fluctuation. Systemic infection, cerebrovascular and other Central nervous system etiology were associated with DSD while metabolic disturbance, organ insufficiency and intracranial neoplasm were associated with the delirium only group. Conclusion The etiology and phenomenology of delirium differs when it occurs in the patient with an underlying dementia. We discuss the implications in terms of identification and management of this complex condition.